2008
DOI: 10.1002/app.28044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inert fillers on diffusion and controlled release of penetrant in polymer matrices

Abstract: This study investigates the characteristics of leaching into a solvent of an active used as termiticide, Bifenthrin 1 (a synthetic pyrethroid) entrapped in polymer, and the effect of layered silicates on this diffusion. Two contrasting solvents, water and acetone, were used to understand this phenomenon; the active is soluble in acetone but has very low solubility in water. The data are used to understand the migration characteristics of Bifenthrin when encapsulated in polyurethane to form a termite barrier. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Termiticides have been found to diffuse from polymeric materials in soil and dry conditions 3. In a previous study, Bifenthrin® was shown to diffuse slowly from the EPU in aqueous media 7. However, the XPS data above indicated that the active fluorine containing group of Bifenthrin® was preferentially on the surface of the EPU.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Termiticides have been found to diffuse from polymeric materials in soil and dry conditions 3. In a previous study, Bifenthrin® was shown to diffuse slowly from the EPU in aqueous media 7. However, the XPS data above indicated that the active fluorine containing group of Bifenthrin® was preferentially on the surface of the EPU.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, the chemical structure of polyurethanes may permit interactions between the host polymer and the active, which would retain the active within the barrier for long periods of time. In a previous paper,7 it has been shown that high levels of Bifenthrin® can be incorporated in the EPU and that the diffusion rates of the active into water from the impregnated polymer are very slow. These results indicate the possibility of extending the life of environmentally friendly pesticides using this concept and limiting the release of actives into the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation